Usefulness of Xpert MTB/RIF Ultra to Rapidly Diagnose Sputum Smear-Negative Pulmonary Tuberculosis Using Bronchial Washing Fluid - Chien, Jung-Yien; Lin, Ching-Kai; Yu, Chong-Jen; Hsueh, Po-Ren (Frontiers in Microbiology, 2020)
This study evaluated the performance of the Xpert MTB/RIF Ultra assay (Xpert Ultra) to detect smear-negative pulmonary tuberculosis (PTB). Xpert Ultra assay was prospectively performed using bronchial washing fluid (BWF) in comparison to COBAS TaqMan MTB (COBAS) assay and mycobacterial culture. Of the 165 enrolled participants, 27 (16.4%) had PTB based on composite reference standard and 16 (9.7%) had culture-confirmed PTB. By the composite reference standard of PTB, the sensitivity of Xpert Ultra (63.0%, 95% confidence interval, CI, 42.4-80.6%) was higher than the COBAS assay (25.9%, P=0.006), BWF-culture (33.3%, P=0.029) and sputum-culture (37.0%, P=0.057). Meanwhile, the specificity of Xpert Ultra was 99.3% which was slightly lower than the 100.0% specificity of the COBAS assay (P=1.000) and cultures (P=1.000). Against the reference standard of culture-confirmed PTB, Xpert Ultra also had a higher sensitivity (62.5%, 95% CI, 35.4-84.8%) than the COBAS assay (31.3%, P=0.077) and was similar to BWF-culture (56.3%, P=0.719) and sputum-culture (62.5%, P=1.000). However, one subject with previously treated old PTB had a false-positive result on the Xpert Ultra assay. This prospective study showed Xpert Ultra assay using BWF had better sensitivity than COBAS assay and mycobacterial cultures but could represent a false positive in patients with inactive old PTB.